Faculty and Librarian Perceptions of Librarians as Researchers: Results from Semi-Structured Interviews - Maureen Babb (The Canadian Association of Professional Academic Librarians, 2021)
Following on the results of an earlier survey, this study explores the perceptions of librarians as researchers according to academic librarians and faculty using semi-structured interviews.  Conducting research is a regular part of the academic librarian role, but one that often faces challenges to its undertaking, and one that is not always recognized.  Exploring perceptions of librarian research helps to understand the current state of librarian research, the barriers faced by librarian researchers, and the value of librarian research.  Fifteen librarians and seven faculty members were interviewed from eight Canadian universities.  The interviews were coded and analysed to identify major themes.  Librarian research was found to be sometimes unsupported and therefore difficult to conduct, but valuable to librarians and the discipline of librarianship.  Additionally, librarian research was found to improve relations between librarians and faculty, and more broadly, was found to create a more collegial academic climate.